1997
DOI: 10.2466/pr0.1997.80.3.787
|View full text |Cite
|
Sign up to set email alerts
|

Is Alexithymia a Culture-Bound Construct? Validity and Reliability of the Japanese Versions of the 20-Item Toronto Alexithymia Scale and Modified Beth Israel Hospital Psychosomatic Questionnaire

Abstract: The possibility remains that alexithymia is a culture-bound construct. The authors examined the validity and reliability of the Japanese versions of the 20-item Toronto Alexithymia Scale and the modified Beth Israel Hospital Psychosomatic Questionnaire, testing two samples of 473 college students and 149 psychiatric outpatients. The face validity and internal consistencies were suggested by factor analysis, adequate internal consistency, relatively high test-retest correlations, and high specificity and sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 24 publications
4
31
0
Order By: Relevance
“…The original authors have suggested a total score of 61 or higher for alexithymia screening. Discriminant validity of this cutoff point among Japanese college students and psychiatric outpatients has been confirmed by Fukunishi et al [36]against the modified version of the Beth Israel Hospital Psychosomatic Questionnaire [37]as a gold standard.…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…The original authors have suggested a total score of 61 or higher for alexithymia screening. Discriminant validity of this cutoff point among Japanese college students and psychiatric outpatients has been confirmed by Fukunishi et al [36]against the modified version of the Beth Israel Hospital Psychosomatic Questionnaire [37]as a gold standard.…”
Section: Methodsmentioning
confidence: 90%
“…Alexithmia was assessed using the Japanese version of the 20-item Toronto Alexithymia Scale (TAS-20) [36]. The TAS-20 is a self-report scale developed by Bagby et al in 1994 [37, 38], and is currently the most frequently used tool to measure alexithymia [12, 15, 18, 39, 40, 41, 42].…”
Section: Methodsmentioning
confidence: 99%
“…All of the participants completed a battery of well-validated self-reporting inventories described below for psychological evaluation. These self-report measures were translated into Japanese using the back-translation method [24,25,26,27]. …”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have suggested that the TAS-20 has adequate validity and reliability [2,3] and that the Japanese version of the TAS-20 also has high construct validity and reliability [18]. In this study, the TAS-20 total score was used as an index of the degree of alexithymia.…”
Section: Zung Self-rating Depression Scale Sdsmentioning
confidence: 99%